Manufacture and Use of Mesoporous Magnesium Silicate for Increasing Vitamin E Concentrate from Candlenut Oil - Bangun, Nimpan; Simanjuntak, Benri (Journal of Chemical Natural Resources, 2022)
Magnesium silicate 75, magnesium silicate 90, and magnesium silicate MgO have been synthesized to increase the concentration of vitamin E from candlenut oil. The reaction of MgO and SiO2 synthesizes the adsorbent magnesium silicate—X H2O by hydrothermal method. The magnesium silicate obtained was characterized by BET, showing the pore size of the three different types of adsorbents, namely magnesium silicate 75 (6.118 nm), magnesium silicate 90 (6.248 nm), and magnesium silicate MgO (3.2238 nm). The adsorbent is used to increase the concentration of vitamin E in candlenut oil. Pecan oil is dissolved with n-hexane in a ratio of 1: 1 in a column containing the adsorbent. After the n-hexane descends from the column tool, vacuum to remove the solvent. Then the results are collected into vials. Then vitamin E levels wer measured by HPLC using standard Tocopherol and tocotrienol. The results of the HPLC test obtained a comparison of the three types of adsorbents' ability to increase levels of vitamin E from candlenut oil, where the adsorbent of magnesium silicate MgO can only increase vitamin E levels which were 429 ppm to 248.72 ppm (0.57 times enriched). In contrast, the magnesium silicate adsorbents 75 and 90 can increase vitamin E levels from 429 ppm to 733.73 ppm (1. 71 times improved) and 855.97 ppm (1.99 times enriched).